Time Use and the Geography of Economic Opportunity - Sulagna Mookerjee; John D. Pedersen; David Slichter (Institute of Labor Economics (IZA), 2022)
The community in which a child is raised has a substantial effect on their income in adulthood. To help understand what is different about communities which produce higher incomes, we document how time use differs between communities which increase vs. decrease incomes. The main differences are that, in areas which produce higher incomes, people spend more time at work, and adults spend more time with children. The data do not support some theories of what makes communities effective at producing human capital: People do not spend more time on educational activities, or on community events and institutions, in areas which increase incomes by more.
Keywords: D13; J22; J24; J62; 330; time use; intergenerational mobility